Упражнения на нестабильных сферах как средство укрепления мышц плеча - Попадюха, Юрий; Марайта, Адель М. А.; Алёшина, Алла; Popadiukha, Yuriy; Marayta, Adele M. A.; Aleshina, Alla (Східноєвропейський національний університет ім. Лесі Українки, 2012)
Травмы мышц плеча происходят как у спортсменов, так и у людей, не занимающихся спортом. Очень часто повреждается ротаторная манжета плеча (РМП), а частота травм повышается при застарелых повреждениях и хронических заболеваниях плечевого сустава (ПС). Комплексное использование современных технологий физической реабилитации (ФР) снижают сроки восстановления после травм плеча. Задачи – анализ особенностей укрепления мышц плеча за счёт выполнения физических упражнений на нестабильных сферах. Результаты: определены особенности укрепления мышц плеча выполнением физических упражнений на нестабильных сферах, которые с успехом могут применяться в процессе ФР при повреждениях ПС человека. Выводы: у человека чаще всего травмируется РМП, эффективным средством восстановления и укрепления мышц плеча при таких травмах является выполнение физических упражнений на нестабильных сферах – фитболе и тренажере «Баланс-Тренер» (ВОSU). Traumas of shoulder muscles as occurring among sportsmen and people how are not practicing sport. Very often rotatory cuff is injured and traumas frequency is increasing in case of inveterate injuries and chronic disease of shoulder joint. Complex usage of modern technologies of physical rehabilitation reduces recovery period after shoulder traumas. Task: to make the analysis of peculiarities of shoulder muscles strengthening by usage of physical exercises on unstable spheres. Results: we have defined peculiarities of shoulder muscle strengthening by practicing physical exercises on unstable spheres that successfully may be applied in the process of physical rehabilitation in case of human shoulder joint injuries. Conclusions: the most frequent injuries are rotatory cuff injuries, an effective means of recovery and strengthening of shoulder muscles on case of such traumas are practicing physical exercises on unstable spheres- football and training equipment «Balance-Trainer».
Exercises on Unstable Areas as Means of Shoulder Muscles Strengthening
Keywords: плечевой сустав; спортсмен; повреждения; нестабильная сфера; тренажёр; укрепление; физические упражнения; shoulder joint; sportsman; injury; unstable sphere; training equipment; strengthening; physical exercises